2014
DOI: 10.1111/cns.12275
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic Terminals Regulate lDOPA‐derived Dopamine Extracellular Levels in a Region‐dependent Manner in Parkinsonian Rats

Abstract: Noradrenalin neurons are indirectly involved in the mechanism of action of L-DOPA in part through the heterologous reuptake of DA in extrastriatal regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…In the striatum of a 6-OHDA-lesioned hemiparkinsonian rat, NET expression increases but norepinephrine tissue content remains the same (Chotibut et al, 2012). Navailles et al (2014) showed in a similar rat model that destruction of norepinephrine fibers using N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine does not potentiate the levodopa effect in the striatum. These results suggest that increased NET is expressed on cells other than norepinephrinergic neurons.…”
Section: The Role Of Norepinephrine Transporters In Reuptake Of Dopammentioning
confidence: 99%
See 1 more Smart Citation
“…In the striatum of a 6-OHDA-lesioned hemiparkinsonian rat, NET expression increases but norepinephrine tissue content remains the same (Chotibut et al, 2012). Navailles et al (2014) showed in a similar rat model that destruction of norepinephrine fibers using N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine does not potentiate the levodopa effect in the striatum. These results suggest that increased NET is expressed on cells other than norepinephrinergic neurons.…”
Section: The Role Of Norepinephrine Transporters In Reuptake Of Dopammentioning
confidence: 99%
“…Navailles et al (2014) showed in 6-OHDA-lesioned rats that the NET blockers desipramine (10 mg/kg) and reboxetine (3 mg/kg) potentiated the levodopa effect in the prefrontal cortex, substantia nigra pars reticulata, and hippocampus, but not in the striatum. They discussed that the contradictory result of Arai et al (2008) is because of their high dose of desipramine (25 mg/kg), in which desipramine non-selectively binds to sites other than NET.…”
Section: The Role Of Norepinephrine Transporters In Reuptake Of Dopammentioning
confidence: 99%
“…Our results are limited to striatal analysis because of the relative abundance of DA neuropil (although lesioned) over other DA regions like substantia nigra. DA uptake in the substantia nigra could also affect LID severity (Navailles et al, 2014), given significant noradrenergic innervation in this region. However, there is comparatively less DAT protein and DA uptake in the substantia nigra, which precluded us from examining this possibility.…”
Section: Norepinephrine Transporter and L-dopa Dyskinesiamentioning
confidence: 99%
“…The second consequence is that striatal DA released by L-DOPA is extremely low for at least three reasons: (i) the density of striatal 5-HT fibers is 10 to 20 times lower compared to the natural density of DA fibers; (ii) 5-HT neurons fire around 1 Hz or below and L-DOPA does not enhance the firing rate of 5-HT neurons (Miguelez et al, 2016b); DA neurons normally fire above 4 Hz (Bunney et al, 1973; Harden and Grace, 1995); (iii) the intraneuronal and neurochemical organization of striatal DA neurons (low metabolism, high rate of translocation into exocytotic vesicles) is specific to the DA terminals of the striatum and is not encountered in 5-HT terminals (De Deurwaerdère et al, 2016). The apparent higher magnitude of response to L-DOPA in the striatum compared to other brain regions simply corresponds to the stronger loss of clearance in the striatum due to the loss of DAT while the clearance of extracellular DA in extrastriatal regions is in part related to the NET (Navailles et al, 2014) (Figure 4). …”
Section: From Pathophysiology To Treatmentsmentioning
confidence: 99%